Extragonadal form of germ cell pineal tumour: a case report - Chilimoniuk, Malgorzata; Olszewska, Ewa; Kiluk, Aneta (Contemporary Oncology/Współczesna Onkologia, 2011)
The pineal region is the most common area for germ cell tumours. They are mostly observed in children. In adults they are more common in men in the second or third decade of life. Pineal tumours have a diverse histopathology. Their growth is slow and the symptoms result from the compression of adjacent cerebral structures. One of the histopathological forms is germinal tumours, including mild or malignant teratoma. They have the ability to release neoplastic markers, e.g. AFP, -HCG, which are used to evaluate the effectiveness of surgical and oncological treatment. The paper presents a case of a 24-year-old man diagnosed as teratocarcinoma. The treatment protocol consisted of both surgery and conventional fractionation radiotherapy (Df = 1.8 Gy, 5 × weekly) to the total dose of 50.4 Gy. After a few months, there was a recurrence of the cancer process. The patient received 2 courses of chemotherapy, which did not yield the expected therapeutic effect. The patient’s prognosis is unfavourable due to rapid local relapse and failure after treatment. The case is presented due to the rarity of pineal teratocarcinoma tumours and the age of the patient.